Spectrophotometric Determination of Trifluoperazine Hydrochloride Using Peak Area - Ali Mohammad Hussein; Nabeel S.Othman (African Journal of Advanced Pure and Applied Sciences, 2023)
The determination of triflouperazine hydrochloride in pure and dose forms has been developed using a simple spectrophotometric approach. Triflouperazine HCl interacted with sulfanilic acid through oxidative coupling. The area under the peak between the two wavelengths of 482-601 was measured and the estimate range was 0.5-100 µg/mL with a coefficient of 99.97 and RSD=1.9498. The method was applied to estimate Triflouperazine HCl in tablets with satisfactory results.